Transforming a hospital's organizational culture to promote parent-child relationships and child development - Mariel Benjamin; Carrie Quinn; Aliza Pressman; Layla Fattah; Rebecca Parlakian; Ellen Galinsky; Blair Hammond (Frontiers in Pediatrics)
IntroductionEarly caregiving interactions and experiences profoundly shape a child's brain development. The American Academy of Pediatrics (AAP) recently advocated for a public-health approach to promoting safe, stable, nurturing relationships that is “founded on universal primary preventions”, including consistent messaging on fostering family resilience, nurturing connections, and positive childhood experiences. Hospitals have unique access to families with children ages 0–5 and therefore play a key role in supporting these early experiences. This project sought to shift the organizational culture of maternity and pediatric units at a hospital towards promoting early relationships and child development through a physical messaging campaign paired with staff training. This study examined whether the messaging campaign and staff training shifted staff's self-reported knowledge, attitudes, and behavior.MethodsNon-physician staff across six pediatric and maternity units in a large urban hospital participated in the intervention. Staff completed surveys before and after message installation and training.ResultsAnalysis of 356 pre-intervention surveys and 320 post-intervention surveys showed significant changes in staff's knowledge, attitudes, and behaviors that promote early learning and parent-child relationships. Most staff also reported feeling more empowered in their work (88%) and that the hospital environment had become a friendlier place for parents and families (89%).DiscussionA messaging and training intervention can create a culture whereby staff support early caregiving and child development in the hospital setting. Further research is needed to understand whether the intervention impacts caregivers and their children.